Study of character development and achievement of wrestling athletes through structured education and training: an autobiography study - Pamungkas, Risma Ayu Putri; Nurrochmah, Siti (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
The sport of wrestling requires a combination of strong physique, good technique, and mental toughness, making it one of the most challenging sports. This study uses a narrative qualitative approach with an autobiographical study method. This study focuses on one main subject, namely the author herself, Rizma Ayu Putri Pamungkas, a national wrestling athlete and student of the Faculty of Sports Science, State University of Malang. The research design used is narrative-descriptive, namely the chronology of life experiences, interviews with informants, document observation, thematic coding, reflection and interpretation. Research results. shows that experience as an athlete not only shapes achievement, but also forms a strong, disciplined, and responsible character. Interpretation of the narrative shows a strong relationship between a structured training system, social support, and ongoing personal development. Athletes are not only judged by medals, but also by their ability to manage stress, injuries, and social and academic pressures. This study shows that achievement in wrestling, especially by female athletes, is the result of synergy between structured physical training, strong social support, and formal education that supports the cognitive development and character of athletes. Further research is recommended to include more subjects from various backgrounds to expand the generalizability of the findings.